Sonochemical-Assisted Deposition Synthesis of Visible-Light-Driven Pd/Bi2MoO6 Used for Photocatalytic Degradation of Rhodamine B - Anukorn Phuruangrat (2020)
© 2020, The Minerals, Metals & Materials Society. Bi2MoO6 nanoplates loaded with different weight contents of Pd were synthesized by sonochemical-assisted deposition. Phase, morphology and photocatalytic properties were studied by x-ray diffraction, scanning electron microscopy, transmission electron microscopy and x-ray photoelectron spectroscopy. The analytical results show that Pd cubic phase of spherical nanoparticles was deposited on the surface of orthorhombic Bi2MoO6 nanoplates. Photocatalysis of rhodamine B as a dye model was tested for photodegradation under visible light irradiation. In this research, Pd/Bi2MoO6 nanocomposites exhibited photocatalytic activity higher than pure Bi2MoO6. Moreover, 5 wt.% Pd/Bi2MoO6 nanocomposites have the highest photocatalytic activity for degradation of RhB under visible light irradiation.